Karakteristik Perjalanan Armada Barang Minimarket di Kota Makassar - Indriaty Wulansari (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
The growth of minimarkets in Makassar city shows very large numbers. The large growth of outlets is in line with the increase in freight transportation (fleet) that will distribute goods. The storage of minimarkets (Alfamart, Alfamidi, and Indomart) is located in the Makassar Industrial Area (KIMA). This research is descriptive-quantitative. The purpose of this study was to determine the characteristics of the transportation of goods for each type of minimarket. The result showed that the departure time for all types of minimarkets was the same between 07.00-18.00 WITA, then the average speed of the fleet range from 35-45 km/hour, and the route is chosen was dominantly toll of the total trips.